The Principles of Psychological Support of the Family with Problem Child - Mushkevych, Myroslava (Psychological Prospects Journal, 2014)
This paper presents a theoretical and empirical analysis of psychological support of families, which have a problem child. Diagnostic and corrective maintenance principles are selected. Different scientific approaches to family with problem child are presented (N. A. Berezan, I. J. Hobod, N. V. Lunchenko, A. G. Obukhov, V. G. Panok, S. L. Radivilovskyy etc.). On the basis of psychological research and with the help of such methods as a theoretical analysis of the scientific literature, conversation, counseling parents, the basic principles of psychological support for families, which have problem children, were allocated: stages (each new stage complements the previous one, promotes the release of the relevant criteria for the operation); continuity (the link between new and old, is a condition cohesion of establishing the zone of proximal development); systemic (set of measures for the development of one family member and the family as a system, that includes three subsystems – the marriage, parental and siblings’); complexity (sales subtotal goals); normalization (maximum approximation of functioning family, wich has a child with problems in development, to the conditions of the functioning of the family with a healthy child); information and methodological assistance (providing parents necessary knowledge and skills for a successful operation, collaboration, interpersonal interaction); multi-modality (the study of the family at four levels – medical, social, individual, environmental); personal orientation (focus on a particular individual, personal approach); scholarship (using results of support for the development of the enhanced maintenance); a state program (development of services for families with problem children and their inclusion in the organic part of the total public support). It is indicated that the use of these principles will help in working with parents, which have problem children, will harmonize their operations not only in the family, but also in the society at all.